THE IMPLEMENTATION OF WHATSAPP – BASED ONLINE LEARNING IN ENGLISH SUBJECT AT MTsN 2 KEDIRI - Alaidi, Nadia (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2023)
This study is conducted to find out: (1) the planning of WhatsApp based online learning in English subject, (2) implementation of WhatsApp based online learning in English subject, (3) the evaluation of WhatsApp based online learning in English subject, (4) students’ response of WhatsApp based online learning in English subject. The instruments used to collect data are interview and documentation. Data validity is done by triangulating sources because the data obtained will be collected and know the truth in this study. Data analysis technique consists of data presentation, data reduction, and drawing conclusions. The results of this research are: the planning of WhatsApp based online learning in English subject carried out by MtsN 2 Kediri are determining the essential material to be given to students, compiling a syllabus, and making lesson plans; the implementation of WhatsApp-based online learning at MtsN 2 Kediri consists of opening activity, core activity, and closing activity. The opening activity, starting with greetings, asking how students are, then continued with the main activity, providing material with features available in WhatsApp. The evaluation of WhatsApp based online learning in English subject at MtsN 2 Kediri are using WhatsApp group, WhatsApp private chat, Google form, and Google classroom. Students’ respond of WhatsApp based online learning in English subject is negative.